(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article discusses the importance of using tongue twisters in developing English lexical and pronunciation skills of primary school students. The study explains effective classroom methods for improving pronunciation, vocabulary, fluency, and speaking confidence through tongue twister activities. The role of interactive exercises and pronunciation practice in English language teaching is also analyzed.